Predictors of prolonged hospitalization among geriatric trauma patients using the modified 5-Item Frailty index in a Middle Eastern trauma center: an 11-year retrospective study - Husham Abdelrahman (768893) (2025)
Background Using a validated tool, we explored the prevalence, risk factors, and predictors of longer hospitalization among hospitalized geriatric patients. Methods Retrospective and comparative analyses of age groups (55–64 vs. ≥ 65 years), gender, survival status, and frailty index categories were performed. The Modified 5-Item Frailty Index was assessed, and multivariable logistic regression analysis was performed to predict prolonged hospitalization (> 7 days). Results There were 17,600 trauma hospitalizations with a mean age of 32 ± 15 years between 2010 and 2021; of them, 9.2% were geriatrics at ≥ 55–64 years (n = 935) and ≥ 65 years (n = 691). The female/male ratio was 17.5%/82.5%, and the mean injury severity score was 13 ± 9. The injury rate for age ≥ 65 was 24 per 10,000 compared to 10 per 10,000 in the younger group age (≥ 55–64). 35% of injuries occurred at home due to falls. Overall mortality was 8%, with a higher rate among males than females (9% vs. 4%). The deceased were three years older at the time of death compared to the survivors. Higher frailty grades were associated with home-related falls and head injuries. Patients 65 years or older were likely to have higher frailty scores, as indicated by higher percentages in the mFI-5. Among the older group, 25% were moderately frail, and 18% severely frail. In the younger group, 50% were frail. Higher frailty scores correlated with increased acute kidney injury, pneumonia, urinary tract infections, and longer hospital stays. Severe frailty significantly predicted longer hospitalization (odds ratio 1.83, p = 0.007). Conclusion One out of eleven trauma admissions was aged > 55. Head injury and bleeding were the leading causes of mortality in the study cohort. There was a significant decrease in the trend of geriatric trauma over the years. The modified FI-5 performs well as a predictive tool of prolonged hospitalization in trauma patients with different age groups. Other Information Published in: European Journal of Trauma and Emergency Surgery License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s00068-024-02742-1